2016
DOI: 10.18632/oncotarget.9757
|View full text |Cite
|
Sign up to set email alerts
|

ATM protein is deficient in over 40% of lung adenocarcinomas

Abstract: Lung cancer is the leading cause of cancer-related mortality in the USA and worldwide, and of the estimated 1.2 million new cases of lung cancer diagnosed every year, over 30% are lung adenocarcinomas. The backbone of 1st-line systemic therapy in the metastatic setting, in the absence of an actionable oncogenic driver, is platinum-based chemotherapy. ATM and ATR are DNA damage signaling kinases activated at DNA double-strand breaks (DSBs) and stalled and collapsed replication forks, respectively. ATM protein i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 37 publications
(50 reference statements)
3
38
0
Order By: Relevance
“…Only very recently, immune checkpoint-blocking antibodies are entering the first-line setting in selected patient populations. To approach these difficult to treat KRAS-mutant tumors, we initially analyzed publicly available cancer genome sequencing data to ask whether we could identify cooccurring genetic aberrations (7). Consistent with previously published data (3), we found that protein-damaging TP53 mutations, MDM2 amplifications, and CDKN2A alterations are frequently detected in KRASmutant lung adenocarcinomas (Fig.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Only very recently, immune checkpoint-blocking antibodies are entering the first-line setting in selected patient populations. To approach these difficult to treat KRAS-mutant tumors, we initially analyzed publicly available cancer genome sequencing data to ask whether we could identify cooccurring genetic aberrations (7). Consistent with previously published data (3), we found that protein-damaging TP53 mutations, MDM2 amplifications, and CDKN2A alterations are frequently detected in KRASmutant lung adenocarcinomas (Fig.…”
Section: Resultssupporting
confidence: 79%
“…These data suggest that an impaired DNA damage response maybe selected in KRASmutant lung adenocarcinoma. In line with this observation, it was recently shown that approximately 40% of human lung adenocarcinomas lack ATM protein expression (7).…”
Section: Introductionmentioning
confidence: 61%
“…In this phase I study, the toxicity profile of veliparib in combination with gemcitabine is consistent with what is typically observed with gemcitabine monotherapy, with myelosuppression (leukopenia, granulocytopenia, thrombocytopenia, anemia) and nausea and vomiting being the most frequent adverse events [21,22]. Liver enzyme elevation, commonly reported with gemcitabine therapy, was also observed.…”
Section: Discussionsupporting
confidence: 82%
“…However, analysis of ATM mutations in Ataxia Telangiectasia, a cancer predisposition syndrome caused by loss or inactivation of both copies of the ATM gene 46 has shown that many mis-sense mutations result in protein truncation 47 . Indeed, immunohistochemistry of ATM protein expression in lung adenocarcinoma revealed that over 40% had low protein expression, despite only 10% showing gene mutation 48 . In addition, ATM promoter methylation has been shown to lead to silencing in some cancer cells 49,50 .…”
Section: Discussionmentioning
confidence: 99%